Dual‐wavelength excitation for fluorescence‐based quantification of zinc protoporphyrin IX and protoporphyrin IX in whole blood. Issue 7 (1st March 2013) - Hennig, Georg; Gruber, Christian; Vogeser, Michael; Stepp, Herbert; Dittmar, Stephan; Sroka, Ronald; Brittenham, Gary M.
Abstract Quantification of erythrocyte zinc protoporphyrin IX (ZnPP) and protoporphyrin IX (PPIX), individually or jointly, is useful for the diagnostic evaluation of iron deficiency, iron‐restricted erythropoiesis, lead exposure, and porphyrias. A method for simultaneous quantification of ZnPP and PPIX in unwashed blood samples is described, using dual‐wavelength excitation to effectively eliminate background fluorescence from other blood constituents. In blood samples from 35 subjects, the results of the dual‐wavelength excitation method and a reference high performance liquid chromatography (HPLC) assay were closely correlated both for ZnPP (rs = 0.943, p < 0.0001; range 37–689 μmol ZnPP/mol heme, 84–1238 nmol/L) and for PPIX (rs = 0.959, p < 0.0001; range 42–4212 μmol PPIX/mol heme, 93–5394 nmol/L). In addition, for ZnPP, the proposed method is compared with conventional single‐wavelength excitation and with commercial front‐face fluorimetry of washed erythrocytes and whole blood. We hypothesize that dual‐wavelength excitation fluorimetry will provide a new approach to the suppression of background fluorescence in blood and tissue measurements of ZnPP and PPIX. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)